Entangled life: How fungi make our worlds, change our minds, and shape our futures - Sheldrake, Merlin (United Kingdom Penguin Random House, 2020)
The more we learn about fungi, the less it makes sense without them. They can change our minds, heal our bodies and even help us avoid environmental disaster; they are metabolic masters, earth-makers and key players in most of nature's processes.